Immune Reactions of Human Blood Platelets - Mueller-Eckhardt, Ch; Lüscher, E. F (Thrombosis and Haemostasis, 1968)
1. Provided they are coated with gammaglobulin, polystyrene latex particles induce in washed human blood platelets the release of adenine nucleotides, aggregation and the contraction of the formed aggregates. Albumin and fibrinogen are unable to replace gammaglobulin in this reaction. Particles with a diameter of about 0.8 μ proved most effective; larger ones were inactive.2. The release of nucleotides is a fast process; it is impaired but not completely inhibited by the removal of Ca++-ions. Aggregation and contraction of the aggregates are absent without Ca++-ions.3. Normal gammaglobulin by itself has scarcely an effect upon platelets and it fixes added hemolytic complement (C’) only to a negligible extent. After the adsorption to latex it acquires strong C’-fixing properties, and becomes more reactive towards platelets. Repeated adsorption of the same gammaglobulin preparation with latex did not change this behaviour, which therefore is due to a property of the gammaglobulin itself, and not of a preferentially adsorbed, C’-activating contaminant. Treatment at pH 4 of gammaglobulin before its adsorption onto latex simultaneously abolished its effects on platelets, and on C.4. It must be concluded that the effect of opsonized latex particles upon blood platelets is unseparable from their C’activating capacity. On the other hand, the addition of C’ not only proved unnecessary; the presence of serum rather impaired the release of nucleotides by latex particles.